Study of Reliability of PC-PVT 2.0 on Sex and Sleep Duration Restrictions Factors - Siswanto, Daniel; Susanto, Sani; Indranila, M.V. (Jurnal Improsci, 2025)
Background.  There are two million workers in Indonesia who died from work accidents caused by fatigue. Fatigue is a contributing factor to accidents, injuries, and deaths. The differences between men and women hinder the relationship between fatigue and gender. On average, women work less hours than men. Aim. Lack of sleep, increased alertness, and longer duration of work can increase a person's fatigue. Someone who experiences sleepiness and fatigue has a strong relationship with decreased alertness. One of the measuring tools used for the evaluation of human awareness is the Psychomotor Vigilance Task (PVT). So the aim of this study is to determine the reliability level of PC-PVT 2.0 on gender and limited sleep duration factors Methods. This study uses Personal Computer (PC) - PVT 2.0 as a tool with three parameters: mean reaction time (RT), minor lapses, and number of false starts as indicators of alertness. The PC-PVT 2.0 tool has not been tested for its reliability in measuring the level of alertness when it is under the influence of sex differences and limited sleep duration. This study involved sixteen participants (eight men and eight women with a mean age of 21.375 1.087) to test PC-PVT 2.0 for 10 minutes with two tests for each treatment. During the PC-PVT 2.0 test, each participant's heart rate data was recorded using the Mi Band 2. Each participant received two treatments, sleep for 4 hours and 8 hours with two repetitions (test-retest). PC-PVT 2.0 testing on the effect of gender and limited sleep duration used two methods: Multivariate Analysis of Variance (MANOVA) and Analysis of Variance (ANOVA). In determining the reliability value, the Intraclass Correlation Coefficient (ICC) method is used with a two-way mixed effect model, definitions of absolute agreement & consistency, and multiple measurement types. Result. ANOVA and MANOVA test results showed that the three parameters of PC-PVT 2.0 affected the differences in sleep treatment conditions, namely lack of sleep (4 hours) and sufficient sleep (8 hours). However, the PC-PVT 2.0 parameter, which had an effect on gender differences, was only valid for the mean RT and minor lapses parameters. The reliability test results showed that the mean RT parameter had an ICC value of > 0.8 for all test categories (male, female, lack of sleep and sufficient sleep) with a good reliability rating category. The minor lapses parameter has an ICC value of > 0.7 for all test categories with sufficient reliability rating categories. Conclusion. This shows that the PC-PVT 2.0 device with the alertness indicator of the mean RT and minor lapse parameters has a high level of reliability when it is under the influence of sex differences and limited sleep duration. Implementation. PC-PVT 2.0 is reliable on Sex and Sleep Duration Restrictions Factors